Utilization of response surface methodology to optimize the mechanical behaviour of flax/nano TiO2/Epoxy based hybrid composites under liquid nitrogen environment - Mohammed Ajmal, Sheriff F.; Natrayan, L.; Giri, Jayant; Makki, Emad; Shah, Mohd Asif; Mallik, Saurav (Frontiers in Materials, 2024)
Linum usitatissimum commonly known as flax fibers, emerges as a promising reinforcement phase for artificial polymer resins, boasting ecological benefits, low density, and easy accessibility. However, the mechanical behavior of such composites hinges crucially on factors such as fiber mat thickness, nanoTiO2 filler content, and the application of cryogenic treatment. Addressing this complex interplay, this study employs a hand lay-up technique for composite construction, subjecting nanocomposite plates to the challenging liquid nitrogen conditions at 77 K post-manufacture. Recognizing the need for an optimized approach, Response Surface Methodology (RSM) based on Box-Benhken designs is employed to enhance the mixing features of linum usitatissimum polymer composites. The study calculates anticipated mechanical strength values through rigorous ANOVA inferential analysis, uncovering the pivotal roles played by fiber mat thickness, nanofiller content, and cryogenic treatment in the two feature interactions (2FI) model components. The methodology proves robust with high R 2 values (0.9670 for tensile, 0.9845 for flexural, and 0.9670 for ILSS) consistently aligning with experimental findings. The study culminates in identifying optimized parameters for maximal mechanical properties-300 gsm flax fiber thickness, 5 wt.% nano TiO2 concentration, and a 15-minute cryogenic treatment-a result that advances our understanding of fundamental factors influencing composite performance and provides practical guidelines for applications in fields requiring superior mechanical strength in challenging environments.